Zaibatsu dissolution in Japan - Bisson, T. A. (University of California Press, 1954)
After describing the pattern of the family business combines which have dominated Japanese economic life, the author discusses the efforts made, under the Occupation, to dissolve them. In addition to the usual complications and disputes involved in anti-monopoly measures there was in this case the further confusing impact of American principles and policies--themselves in a state of flux--upon Japan's practices. The author gives a lucid account, while indicating his own preference for an extension of public ownership as the most appropriate line of action in the Japanese case.